2021
DOI: 10.1080/07853890.2021.1896071
|View full text |Cite
|
Sign up to set email alerts
|

Strategies used by nurses and tracheostomized users in communication: systematic review

Abstract: Introduction: In Europe 20% of the working population is somehow involved in shift work. Studies show that it can have a negative impact on workers' health and well-being, with direct consequences on performance and efficiency [1]. Nurses are among health professionals with a higher risk of burnout [2], which can negatively affect their alertness, attention and concentration, with direct consequences on patient's health [3]. The aim of this study is to identify relevant factors regarding the impact of shift wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…3,16 In another systematic review, it was found that caregivers try to speak slowly, use facial expressions, and use verbal and nonverbal communication techniques such as writing, reading, and explanatory cards when communicating with their patients. 15 In accordance with the literature, the caregivers in our study stated that they used verbal and nonverbal communication techniques such as gestures and facial expressions, writing, showing letters, eye contact, and touch to communicate with their patients. Although all these verbal and nonverbal methods can be used when communicating with tracheostomy patients, it may be challenging for the patients in terms of the required coordination and physical and mental strength.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…3,16 In another systematic review, it was found that caregivers try to speak slowly, use facial expressions, and use verbal and nonverbal communication techniques such as writing, reading, and explanatory cards when communicating with their patients. 15 In accordance with the literature, the caregivers in our study stated that they used verbal and nonverbal communication techniques such as gestures and facial expressions, writing, showing letters, eye contact, and touch to communicate with their patients. Although all these verbal and nonverbal methods can be used when communicating with tracheostomy patients, it may be challenging for the patients in terms of the required coordination and physical and mental strength.…”
Section: Discussionsupporting
confidence: 78%
“…14 Researchers have recommended using verbal and nonverbal communication techniques to address this challenge. 15 A systematic review found that lipreading, touch, eye contact, gestures, and mimicking were used. 3,16 In another systematic review, it was found that caregivers try to speak slowly, use facial expressions, and use verbal and nonverbal communication techniques such as writing, reading, and explanatory cards when communicating with their patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same study highlighted anger and frustration as feelings also experienced by nurses when they were not able to recognise what the patient needed or what they were trying to communicate. Other studies have found that despite the existence of several communication techniques to assist in the communications between mechanically ventilated patients and other health professionals, there is currently some difficulty in teaching them to communicate (Duarte et al, 2021).…”
Section: Disrupted Communication Between Patients and Nurses Due To U...mentioning
confidence: 99%